Performance analysis of solar powered airport based on energy and exergy analysis - Sukumaran, Sreenath; Sudhakar, K. (Elsevier Ltd, 2018)
In this paper, performance analysis of 12 MWp grid interactive solar photovoltaic power plant, located at Cochin International Airport, India is carried out using energy and exergy analysis. The thermal performance of the PV plant installed within the airport premises has been investigated based on actual weather data and monitored values of the plant. In order to evaluate the exergy and energy performance of the PV plant, a parametric approach with destruction is applied. The energy efficiency of the plant varied between 16.4% and 13.33% and its value depends on the electrical energy output and insolation only. The annual average exergy efficiency is found to be 9.77%. Theoretically, cost of exergy destruction in terms of unit electricity cost is estimated. The thermal destruction is huge in an MW scale solar PV plant. A considerable amount of thermal losses (4.44 MW) can be avoided by integrating cooling technique to the SPV system. Thus the thermodynamic analysis of PV system provides more clarity about system performance and serves as a useful reference for future PV power plants in an airport environment.